Integrated PET/MRI With 68Ga-DOTATATE and 18F-FDG in Pheochromocytomas and Paragangliomas: An Initial Study. (8th April 2022) - Xu, Si; Pan, Yu; Zhou, Jinxin; Ju, Huijun; Zhang, Yifan
Abstract : Purpose: Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumors with metastatic potential. Both 68 Ga-DOTATATE and 18 F-FDG PET/CT scans have been demonstrated to have important roles in imaging PPGLs, but less is known about the performance of PET/MRI for PPGLs. The study is aimed to investigate whether diffusion-weighted imaging–MRI (DWI-MRI) has an added value to PET imaging in the identification of PPGL lesions by means of integrated PET/MRI. Methods: Eleven patients who underwent both 18 F-FDG and 68 Ga-DOTATATE PET/MRI within 2 weeks were retrospectively included in the study. A total of 56 PPGL lesions were analyzed, and lesion-based detection rates of 68 Ga-DOTATATE PET, 18 F-FDG PET, DWI-MRI, and PET/MRI were calculated and compared, respectively. Results: 68 Ga-DOTATATE PET was superior to 18 F-FDG PET and DWI-MRI in imaging PPGLs with a lesion-based detection rate of 96.4% (54/56) (95% confidence interval [CI], 87.7%–99.6%), 85.7% (48/56) (95% CI, 76.3%–95.2%), and 89.3% (50/56) (95% CI, 80.9%–97.6%), respectively. PET/MRI with DWI could improve the detection rate of 68 Ga-DOTATATE and 18 F-FDG PET alone up to 100% in metastatic PPGLs. Lesions of PPGL demonstrated markedly higher tracer uptake in 68 Ga-DOTATATE PET than in 18 F-FDG PET ( P = 0.009 for primary lesion, P = 0.033 for metastases). Conclusions: 68 Ga-DOTATATE PET showed a higher detection rate than 18 F-FDG for PPGLs. In integrated PET/MRI, MRI had an added value to 18 F-FDG PET but not much to 68 Ga-DOTATATAE PET in identifying PPGL lesions.